1958
DOI: 10.4039/ent90721-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humidity on Mortality and Rate of Development of Immature Stages of the Grain-Infesting Mite Tyrophagus castellanii (Hirst) (Acarina: Acaridae) Reared on Mould Cultures

Abstract: It was observed that populations of Tyrophagus castellanii (Hirst) reared on cereal flakes and yeast for studies of predator-prey interactions were feeding on moulds rather than on the food material, and that an increase in humidity increased their rates of development. To discover whether this was caused by the direct effect of humidity on the mites or by a greater supply of fresh food brought about by an increase in humidity, rearings were made with a technique developed by Rivard (1958). The mites were rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

1963
1963
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
(1 reference statement)
1
10
1
Order By: Relevance
“…This mycelium would act as shelter for the mites to avoid water loss under dry environments. Also, the water content of the fungi employed by Rivard (1958bRivard ( , 1959Rivard ( , 1961 is much higher than that found in the Brewer's yeast flakes of our study, as they are living organisms. Moreover, the composition of the substrate employed to rear the fungi was wheat germ powder and water (Rivard 1958a), which further increases the moisture content.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This mycelium would act as shelter for the mites to avoid water loss under dry environments. Also, the water content of the fungi employed by Rivard (1958bRivard ( , 1959Rivard ( , 1961 is much higher than that found in the Brewer's yeast flakes of our study, as they are living organisms. Moreover, the composition of the substrate employed to rear the fungi was wheat germ powder and water (Rivard 1958a), which further increases the moisture content.…”
Section: Discussioncontrasting
confidence: 57%
“…The comparison of our results with those obtained by Rivard (1958bRivard ( , 1959Rivard ( , 1961 and Cunnington (1969) on T. putrescentiae could serve to show how mites are able to counteract low humidity environments with feeding and behavioural strategies. Thus, whereas we have recorded a relative humidity of 70% to kill all immature stages of T. putrescentiae, these authors reported that it was necessary to reduce the relative humidity to 60% to eliminate the immature stages of this mite.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations